Deciphering the mechanistic roles of ADARs in cancer pathogenesis, tumor immune evasion, and drug resistance - Wang, Xiaoke; Yin, Fei; He, Yangfang; Qiao, Yue; Yan, Yan; Ma, Jingru (Frontiers in Immunology, 2025)
RNA is a fundamental biological macromolecule that undergoes several post-transcriptional modifications, including adenosine to inosine (A-to-I) editing by adenosine deaminases acting on RNA (ADARs). These essential enzymes catalyze the conversion of A-to-I in double-stranded RNA (dsRNA) molecules, influencing RNA stability, splicing, and translation, all of which impact various cellular functions. More recently, RNA editing has emerged as a pivotal mechanism in cancer biology, where ADARs, primarily ADAR1 and ADAR2, exert context-dependent roles as either oncogenic drivers or tumor suppressors. Beyond their catalytic editing function, ADARs also regulate cancer-relevant pathways through editing-independent mechanisms, including RNA binding and protein-protein interactions. Dysregulated ADAR activity facilitates carcinogenesis by altering oncogene expression, impairing tumor suppressor pathways, and reprogramming the transcriptome to promote tumor progression. Furthermore, RNA editing may contribute to tumor cell immune evasion by affecting interferon signaling and altering neoantigen presentation, as well as modulating immune surveillance. Additionally, ADAR-mediated RNA modifications contribute to therapy resistance by modifying drug targets and pathways involved in cell survival and repair. This review comprehensively analyzes the multifaceted roles of RNA-editing ADAR enzymes in cancer pathogenesis, emphasizing editing-dependent and -independent mechanisms contributing to tumor progression, immune evasion, and resistance to therapy. Moreover, we highlight the potential of ADARs as prognostic biomarkers and promising therapeutic targets in oncology. This review aims to spark novel precision oncology and cancer immunotherapy strategies by bridging molecular insights with translational applications.